2015
DOI: 10.5792/ksrr.2015.27.4.274
|View full text |Cite
|
Sign up to set email alerts
|

Compression of the Popliteal Artery after Posterior Cruciate Ligament Reconstruction Using the Tibial Inlay Technique

Abstract: Popliteal artery compression rarely occurs after posterior cruciate ligament (PCL) reconstruction using the tibial inlay technique that allows for direct visualization of the surgical field. However, we experienced a popliteal artery compression after PCL reconstruction performed using the technique, which eventually required re-operation. Here, we report this rare case and discuss reasons of popliteal artery compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Arthroscopic suture fixation techniques can be classified by types of portals and suture material, and by the number of tibial tunnels for suture passage and fixation [2,3,[7][8][9]. The method described here uses a posterior transseptal portal connected to the posteromedial and posterolateral portals [10,15]. Most other techniques use one or two posteromedial portals for visualization and an instrument entrance for the procedure [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic suture fixation techniques can be classified by types of portals and suture material, and by the number of tibial tunnels for suture passage and fixation [2,3,[7][8][9]. The method described here uses a posterior transseptal portal connected to the posteromedial and posterolateral portals [10,15]. Most other techniques use one or two posteromedial portals for visualization and an instrument entrance for the procedure [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…Papalia et al in their systematic review showed the possibility of post-operative hematoma formation due to the larger posterior exposure as well as traction neuropraxia to the saphenous nerve from prolonged retractor placement [14]. Recent studies by Seo et al have demonstrated the possibility of popliteal artery compression if the tibial bone block is placed too far laterally or not adequately recessed in the prepared tibial trough [15]. Furthermore, the risk of neurovascular injury may be increased in the setting of multiligamentous knee injuries with prior vascular repair due to scar tissue formation and altered anatomy.…”
Section: Complicationsmentioning
confidence: 99%
“…Greatly displaced avulsed fractures of the PCL tibial attachment point are traditionally managed mostly by open reduction and hollow screw internal xation [2]. Even in case of minimal displacement, the risk of nonunion or malunion causes multiple surgeons to consider surgery [3,4]. However, the traditional operative procedure for PCL tibial avulsion fractures remains di cult because of the deep lesion localization and complex adjacent anatomical structures, with most of them involving small bone fragments.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of arthroscopy technology and instruments, PCL tibial avulsion fractures are currently more often treated by arthroscopic procedures rather than an open approach [7][8][9]. Biomechanical evidence suggests no signi cant differences in maximum load and stiffness in cases with PCL tibial avulsion fractures administered suture and screw xation [4,10].…”
Section: Introductionmentioning
confidence: 99%